Impact of bedbug’s infestation on use of mosquito nets in malaria control in Matayos, Busia, Kenya - Chebii, Kiptanui; Injera, Wilfred E.; Juma, Kelvin K.; Odiwuor, Collins A.; Ogombo, Concilia (International Journal Of Community Medicine And Public Health, 2025)
Background: Malaria is a significant public health problem in Kenya with more than 70% of its population at risk. The Kenya government has prioritized the provision of long-lasting insecticidal nets (LLINs) and insecticide treated nets (ITNS) in prevention of malaria. However; communities in Matayos, Busia County have shown reluctance in using them, that they harbor bed bugs. This study aims to establish the impact of bedbugs on use of mosquito nets in malaria control. Methods: This was a cross-sectional study carried out at Murende community unit, Matayos, Busia Kenya. A questionnaire was used to collect data. Data analysis was done using SPSS; descriptive statistics were summarized as frequencies and proportions. Chi square was done to measure associations between variables. Results: 77 (respondents) were included in the study. Majority (65%) were females (85%) reported having mosquito nets whereas 15% did not have mosquito nets. Of the 85% with mosquito nets, 78% use them while 22% do not use them. 79% of those who don’t use mosquito nets claimed that mosquito nets harbored bedbugs. There is association between presence of bed bugs and use of mosquito nets (p=0.001), there is association between the level of education and presence of beg bugs (p=0.001) Conclusions: Bedbug infestation is a barrier to consistent and persistent utilization of mosquito nets and has discouraged a bigger population from using them. Concerted effort towards the control of bedbugs has to be made if collateral benefit in malaria control by use of LLINs is to be achieved.